Monitoring Of The Maintenance Of State-Owned Goods In The Form Of Operational Vehicles Of Padjadjaran University For Educational Processing - Ramaditya, Mochamad; Muttaqin, Zainal; Nurzaman, R Adi (Universitas Muhammadiyah Sumatera Utara, 2024)
Unpad is a university that has the status of a State University with Legal Basis (PTN BH) that applies the Public Service Agency Financial Management pattern (PK BLU) or PTN Legal Entity. Unpad obtained the mandate to increase autonomy to become a Legal Entity PTN. Unpad revenue sourced from the State Budget is used to fund operational costs, lecturer costs, education personnel costs, investment costs and development costs. Budget funding issued to be allocated to various financing, one of which is mentioned in Article 5 letter d of Government Regulation No. 26 of 2015 concerning Forms and Mechanisms of Funding for Legal Entity State Universities and is used for the procurement of facilities and infrastructure for the implementation of the tridharma of Higher Education in the form of operational service vehicles. There are several visible problems related to operational vehicles owned by Universitas Padjadjaran that are not suitable for use. Padjadjaran University's operational service vehicles are one example of goods owned by Unpad that need to be maintained and maintained. Since the beginning of its procurement, official vehicles owned by Padjadjaran University are used to support the smooth creation of good mobility in the Padjadjaran University campus environment